Protocol for investigating astrocytic mitochondria in neurons of adult mice using two-photon microscopy - Jian Zhou; Fengling Du; Fan Zhang; Xianhui Zhang; Yuanyuan Wu; Lifang Zhang; Ping Liao; Tianqi Tu; Jianhua Peng; Tao Li; Yong Jiang (STAR Protocols)
Summary: Under pathological conditions, astrocytes can transfer mitochondria to neurons, where they exert neuroprotective effects. In this context, we present a protocol for capturing astrocytic mitochondria in neurons of adult mice using a two-photon microscope. We describe an approach for constructing a mouse model with combined labeling of astrocytic mitochondria and neurons. We then detail procedures for the preparation of a coverslip with a customized titanium ring and cranial window for two-photon microscopy scanning.For complete details on the use and execution of this protocol, please refer to Zhou et al. 1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.